The Impact of a Positive Learning Environment in Elementary Education - Letchworth II, Stuart Bryan (My University, 2025)
As both a teaching student and a creative endeavor pursuant, I believe that stories shape the way we understand the world, as well as the classroom. Belong began as a Signature Honors Project with the intention of showcasing the emotional and academic transformation a child experiences when welcomed into a positive learning environment. Based around my experiences as an education major and intern, I envisioned a story that would reflect what it feels like to be the new kid: nervous, overwhelmed, and unsure of one’s place. But as the child in the story is loved, supported, and invited into community, the world around her becomes brighter, both literally and figuratively. This book uses the metaphor of color to explore belonging, and in doing so, hopes to inspire educators to reflect on the environments they create for their students.
Keywords: Expressive; Adaptive